2021
DOI: 10.1021/acs.biomac.1c00923
|View full text |Cite
|
Sign up to set email alerts
|

Nitrile-Functionalized Poly(2-oxazoline)s as a Versatile Platform for the Development of Polymer Therapeutics

Abstract: In recent years, polymers bearing reactive groups have received significant interest for biomedical applications. Numerous functional polymer platforms have been introduced, which allow for the preparation of materials with tailored properties via post-polymerization modifications. However, because of their reactivity, many functional groups are not compatible with the initial polymerization. The nitrile group is a highly interesting and relatively inert functionality that has mainly received attention in radi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 68 publications
3
21
0
1
Order By: Relevance
“…The reported nitrile side chain functionalized PBuNiOx 85 was found to be thermally stable up to at least 350 °C which is in line with other PAOxs with linear alkyl side chains. The polymer showed amorphous behaviour with a T g of 18.5 °C as observed from DSC.…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…The reported nitrile side chain functionalized PBuNiOx 85 was found to be thermally stable up to at least 350 °C which is in line with other PAOxs with linear alkyl side chains. The polymer showed amorphous behaviour with a T g of 18.5 °C as observed from DSC.…”
Section: Introductionsupporting
confidence: 82%
“…9). 85 CROP also provides straightforward access of PAOxs with 'clickable handles' in the side chain, such as alkene and alkyne groups, as well as in the chain ends, that can be further employed for postpolymerization modification to construct various functional PAOxs via thiol-ene, 105 thiol-yne and copper(I)-catalysed 'click' reactions. 106…”
Section: Poly(2-oxazoline)s Prepared By Crop Of 2-oxazoline Monomersmentioning
confidence: 99%
See 2 more Smart Citations
“…This nitrile group is not only compatible with the polymerization conditions but also allowed for the introduction of amidoxine moieties into polyoxazolidones, which were shown to release nitric oxide intracellularly in BV-2 microglia. 16 One of the main limitations for the biomedical applications of polyoxazolidones is their lack of biodegradability. In this regard, Hadjichristidis and co-workers found that organocatalysis can be used to prepare biodegradable alternatives to poly(2-oxazoline)s by the ring-opening polymerization of Na c y l a t e d 1 , 4 -o x a z e p a n -7 -o n e s .…”
mentioning
confidence: 99%